(Re)Producing Nation: Race, Gender, Sexuality, The Sovereign and the Living Constitution - Hodes, Caroline (Atlantis, 2010)
This paper touches on some of the key themes of the author's dissertation project. It discusses identity construction in constitutional discrimination claims and the possibility of creating an anti-subordination framework from fragments of the existing Canadian and American equality jurisprudence.